2015
DOI: 10.1037/a0037373
|View full text |Cite
|
Sign up to set email alerts
|

“He who can, does; he who cannot, teaches?”: Stereotype threat and preservice teachers.

Abstract: Stereotype threat is defined as a situational threat that diminishes performance, originating from a negative stereotype about one's own social group. In 3 studies, we seek to determine whether there are indeed negative stereotypes of students who have chosen a career in teaching, and whether the performance of these students is affected by stereotype threat. Responses to open-ended questions (Study 1, N = 82) and comparisons in closed-ended response format (Study 2, N = 120) showed that preservice teachers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
(76 reference statements)
1
22
0
4
Order By: Relevance
“…Stereotypes can be defined as shared beliefs about traits that are characteristic of members of a certain social category (e.g., Greenwald and Banaji, 1995 ). Although they may facilitate human behavior and decision-making in complex environments, they often come along with negative effects for the stereotyped group (e.g., Steele and Aronson, 1995 ; Schmader et al, 2004 ; Ihme and Möller, 2015 ). Concerning math, prior studies on gender stereotypes have repeatedly found support for the prevalence of the stereotype endorsing that math would be a typically male domain (e.g., Nosek et al, 2002 ; Steffens et al, 2010 ; Cvencek et al, 2011 ; Steffens and Jelenec, 2011 ; but see Plante et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stereotypes can be defined as shared beliefs about traits that are characteristic of members of a certain social category (e.g., Greenwald and Banaji, 1995 ). Although they may facilitate human behavior and decision-making in complex environments, they often come along with negative effects for the stereotyped group (e.g., Steele and Aronson, 1995 ; Schmader et al, 2004 ; Ihme and Möller, 2015 ). Concerning math, prior studies on gender stereotypes have repeatedly found support for the prevalence of the stereotype endorsing that math would be a typically male domain (e.g., Nosek et al, 2002 ; Steffens et al, 2010 ; Cvencek et al, 2011 ; Steffens and Jelenec, 2011 ; but see Plante et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ihme and Möller (2015) found empirical support for the presence of these paternalistic stereotypes in a multi-study paper. First, they asked pre-service teachers about typical characteristics ascribed to their profession in an open-ended survey.…”
Section: Theorymentioning
confidence: 81%
“…We argue that this may also activate downward social comparisons if the person described is part of a relevant outgroup. As psychology students and pre-service teachers are perceived to be similarly warm, yet different in competence ( Ihme and Möller, 2015 ), social comparison processes are likely to occur.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the findings regarding teacher competence and status into consideration, it is problematic that teachers and pre-service teachers (university students in teacher training) are stereotyped in a paternalistic way with low competence and high warmth (Ihme and Möller, 2015). Teachers and preservice teachers seem to have internalized this paternalistic stereotype and report it themselves (Carlsson and Björklund, 2010;Ihme & Möller, 2015) although no or only small differences compared to other groups of professionals and students in characteristics such as intelligence, motivation, and personality traits were found (Roloff Henoch et al, 2015). Paternalistic stereotypes are connected to emotions like pity, sympathy, and implicit condescension and can, in turn, lead to behavioral tendencies of avoiding and psychological distancing (Cuddy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%